ANALISIS KESIAPAN GURU SEKOLAH DASAR PADA KEMAMPUAN LITERASI DIGITAL DI ERA 4.0 - Lisda, Lisda Erma Melinda; Nailah, Nailah Tresnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The era of the industrial revolution 4.0 requires elementary school teachers to have good digital literacy in order to be able to integrate technology into learning. This study aims to analyze the readiness of elementary school teachers towards digital literacy skills that include aspects of skills, ethics, security, and digital culture. This study uses a qualitative descriptive approach with three high-grade teachers at SDN Kesenden, Cirebon City as subjects. Data collection techniques include observation, interviews, and questionnaires with analysis using the Miles and Huberman model. The results of the study indicate that teachers have sufficient understanding of the concept of digital literacy, and have utilized digital technology in the learning process. However, there are still obstacles in terms of security and maximum utilization of ICT. This study concludes that although teachers show readiness for digital literacy 4.0, further training is needed to strengthen digital literacy competencies as a whole in today's digital era.